Reprogramming of Lipid Metabolism as a New Driving Force Behind Tauroursodeoxycholic Acid-Induced Neural Stem Cell Proliferation - Fernandes, Marta B.; Costa, Márcia; Ribeiro, Maria Filipe; Siquenique, Sónia; Sá Santos, Sónia; Martins, Joana; Coelho, Ana V.; Silva, Margarida F. B.; Rodrigues, Cecília M. P.; Solá, Susana (Frontiers in Cell and Developmental Biology, 2020)
Recent evidence suggests that neural stem cell (NSC) fate is highly dependent on mitochondrial bioenergetics. Tauroursodeoxycholic acid (TUDCA), an endogenous neuroprotective bile acid and a metabolic regulator, stimulates NSC proliferation and enhances adult NSC pool in vitro and in vivo. In this study, we dissected the mechanism triggered by this proliferation-inducing molecule, namely in mediating metabolic reprogramming. Liquid chromatography coupled with mass spectrometry (LC-MS) based detection of differential proteomics revealed that TUDCA reduces the mitochondrial levels of the long-chain acyl-CoA dehydrogenase (LCAD), an enzyme crucial for β-oxidation of long-chain fatty acids (FA). TUDCA impact on NSC mitochondrial proteome was further confirmed, including in neurogenic regions of adult rats. We show that LCAD raises throughout NSC differentiation, while its silencing promotes NSC proliferation. In contrast, nuclear levels of sterol regulatory element-binding protein (SREBP-1), a major transcription factor of lipid biosynthesis, changes in the opposite manner of LCAD, being upregulated by TUDCA. In addition, alterations in some metabolic intermediates, such as palmitic acid, also supported the TUDCA-induced de novo lipogenesis. More interestingly, a metabolic shift from FA to glucose catabolism appears to occur in TUDCA-treated NSCs, since mitochondrial levels of pyruvate dehydrogenase E1-α (PDHE1-α) were significant enhanced by TUDCA. At last, the mitochondria-nucleus translocation of PDHE1-α was potentiated by TUDCA, associated with an increase of H3-histones and acetylated forms. In conclusion, proliferation of NSCs involves metabolic plasticity and mitochondria-nucleus crosstalk, in which nuclear PDHE1-α is required to assure pyruvate-derived acetyl-CoA for histone acetylation and NSC cycle progression.